1998
DOI: 10.1021/np9702291
|View full text |Cite
|
Sign up to set email alerts
|

5-Methoxyjusticidin A, a New Arylnaphthalene Lignan from Protium unifoliolatum

Abstract: A new arylnaphthalene lignan, 9-(1,3-benzodioxol-5-yl)-4,5,6, 7-tetramethoxynaphtho[2,3-C]furan-1(3H)-one (5-methoxyjusticidin A, 1), was isolated from a Et2O extract of the wood of Protium unifoliolatum. The structure of 1 was determined by both spectroscopic and X-ray crystallographic methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
(12 reference statements)
0
9
0
Order By: Relevance
“…433.0899)). The UV spectrum was typical for an arylnaphthalene system; and IR bands at 1764 and 934 cm À1 suggested the presence of a g-lactone and a OCH 2 O group, respectively [9]. In the 1 H-NMR spectrum of 1 ( Table 1), there were four aromatic H-atoms: one signal appeared at d(H) 6.67 (s, HÀC(8)) 1 ), together with an ABX system characteristic of a 1,3,4-trisubstituted aromatic unit (d(H) 6.95 (d, J = 7.8, 1 H); 6.66 (dd, J = 7.8, 1.5, 1 H); 6.77 (d, J = 1.5, 1 H)).…”
mentioning
confidence: 99%
“…433.0899)). The UV spectrum was typical for an arylnaphthalene system; and IR bands at 1764 and 934 cm À1 suggested the presence of a g-lactone and a OCH 2 O group, respectively [9]. In the 1 H-NMR spectrum of 1 ( Table 1), there were four aromatic H-atoms: one signal appeared at d(H) 6.67 (s, HÀC(8)) 1 ), together with an ABX system characteristic of a 1,3,4-trisubstituted aromatic unit (d(H) 6.95 (d, J = 7.8, 1 H); 6.66 (dd, J = 7.8, 1.5, 1 H); 6.77 (d, J = 1.5, 1 H)).…”
mentioning
confidence: 99%
“…The UV spectrum was typical for arylnaphthalene. 4 The IR spectrum showed hydroxyl (3423 cm 21 ), g-lactone (1752 cm 21 ) and aromatic (1624 cm 21 ) absorption bands. 5,6 The 1 H NMR spectrum of 1 exhibited the presence of five aromatic protons, two singlets at d 8.94 (1H, s) and 7.34 (1H, s), and three ABX system protons at d 7.03 (1H, d, J ¼ 7.6 Hz), 7.14 (1H, d, J ¼ 7.6 Hz), and 7.12 (1H, s).…”
Section: Resultsmentioning
confidence: 96%
“…(7) 6.18 (s) --C(7)ÀOCH 2 OÀC (8 Table 2. suggested that it was an arylnaphthalide lignan with a g-lactone unit [9]. From the 1 Hand 13 C-NMR data (Tables 1 and 2) in combination with further results from HSQC and HMBC spectra (Fig.…”
mentioning
confidence: 90%
“…The UV maxima at 204 and 259 nm and the IR (KBr) absorption bands at 3462 and 936 cm À1 suggested that it was also an arylnaphthalide lignan with a g-lactone unit [9]. After analyses of the (Fig.…”
mentioning
confidence: 99%